2022
DOI: 10.15252/msb.202110673
|View full text |Cite
|
Sign up to set email alerts
|

High diversity in Delta variant across countries revealed by genome‐wide analysis of SARS‐CoV‐2 beyond the Spike protein

Abstract: The highly contagious Delta variant of SARS‐CoV‐2 has become a prevalent strain globally and poses a public health challenge around the world. While there has been extensive focus on understanding the amino acid mutations in the Delta variant’s Spike protein, the mutational landscape of the rest of the SARS‐CoV‐2 proteome (25 proteins) remains poorly understood. To this end, we performed a systematic analysis of mutations in all the SARS‐CoV‐2 proteins from nearly 2 million SARS‐CoV‐2 genomes from 176 countrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…This is similar to previous studies indicating the I82T mutation as one of the most frequent mutations in the M protein in the USA, with a 116-fold increase from October 2020 to February 2021 [32]. Suratekar et al also reported I82T as one of the most prevalent mutations in the Delta variant in a systematic analysis of mutations from nearly 2 million SARS-CoV-2 genomes from 176 countries [33]. However, till 2020, D3G was reported as the most common mutation in this protein [22].…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to previous studies indicating the I82T mutation as one of the most frequent mutations in the M protein in the USA, with a 116-fold increase from October 2020 to February 2021 [32]. Suratekar et al also reported I82T as one of the most prevalent mutations in the Delta variant in a systematic analysis of mutations from nearly 2 million SARS-CoV-2 genomes from 176 countries [33]. However, till 2020, D3G was reported as the most common mutation in this protein [22].…”
Section: Discussionsupporting
confidence: 88%
“…It is of note that the different subtypes of the Delta variant present frequent relevant mutations also in proteins different from Spike such as I82T in the M protein, which is apparently specific of Delta (Suratekar et al, 2022 ). This mutation appeared in Italy in April 2021 and has risen to over 90% in December 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The Omicron variant presents a large number of mutations, some of which have been reported in other VOCs such as S477N (B.1 variant); H69/V70 and P681H (Alpha variant); H655Y (Gamma variant); K417N (Beta variant and AY variants); T478K (Delta variant); A701V (Beta and Iota variants); and R346K (Mu variant) (Suratekar et al, 2022). A notable mutation identified in the genomes of Omicron sequenced in this study occurs in residue E484, a key player in immune escape (Laurini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As of February 2022, the most recent SARS-CoV-2 strains declared variants of concern (VoC) by the U.S. Centers for Disease Control and Prevention are Omicron (strain B.1.1.529) and Delta (strain B.1.617.2) ( 7 ). Beyond striking amino acid mutations in the spike protein, Omicron also harbors P13L, Δ31–33, R203K, and G204R nucleocapsid mutations, while Delta strains carry D63G, R203M, and D377Y nucleocapsid mutations ( 8 , 9 ). However, the limits of detection (LoDs) of many FDA EUA antigen tests were established with gamma-irradiated or heat-inactivated preparations of the USA WA1/2020 (WA1) strain ( 10 ) lacking these nucleocapsid mutations.…”
Section: Lettermentioning
confidence: 99%